Pengembangan Aplikasi Gim Untuk Pengenalan Cagar Budaya Di Kota Malang Menggunakan MDA Framework - Rizky Afwan Austin; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Malang City is one of the tourist cities in East Java. In this city, there are many places that can be used as tourist destinations, such as culinary tours, religious tours, to historical tours. There are historical places that are included in the list of cultural heritage in Malang City that have high historical value. To be able to introduce this cultural heritage and increase public interest in history, a medium is needed. One way is through playing video games. The type of game to be developed is a snake and ladder board game. To make it look more modern, this game uses augmented reality features. In this game, players can find out the history and general information of several cultural heritages in Malang. This game is designed using the MDA framework to find out what the player feels after playing and how the player interacts with the game mechanics. To determine the right mechanic, the design was carried out three times. After the design phase is complete, then enter the implementation stage where the game is developed. At this stage, the game is developed using Unity software while 3D forms of cultural heritage objects are created using the SketchUp software. After the implementation phase is complete, then enter the testing phase. This stage is carried out using two types, namely Black-box Testing and Game Experience Questionnaires. The purpose of the Black-box Testing test is to ensure that all functions contained in the game run as expected. Game Experience Questionnaire aims to find out the player's experience after playing this game. Game Experience Questionnaire testing is done by giving questionnaires to players. The contents of the questionnaire are based on the modules in the Game Experience Questionnaire, namely the Core Module and Social Presence Module. The average value of the Core Module and Social Presence Module is 2, which means this game gets a sufficient score.